1969
DOI: 10.1126/science.166.3906.741
|View full text |Cite
|
Sign up to set email alerts
|

Zircon Ages of Felsic Volcanic Rocks in the Upper Precambrian of the Blue Ridge, Appalachian Mountains

Abstract: Five Zirconi samples from Pennsylvania, Virginia, and North Carolina yield discordant uranium-lead ages which suggest an original age of 820 million years and an episodic lead loss at 240 million years. The indicated age of lead loss is interpreted as the age of movement of the Blue Ridge thrust sheet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…He concluded that the rhythmites were deposited in quiet water and reflected volcanic cycles, not glaciation. Rankin (1967Rankin ( , 1969 suggested a glacial origin for the laminated pebbly mudstones and associated muddy-matrix conglomerates (diamictites), a conclusion supported by Blondeau and Lowe (1972), Schwab (1976), and Miller (1986, 1989a.…”
Section: Previous Workmentioning
confidence: 92%
See 2 more Smart Citations
“…He concluded that the rhythmites were deposited in quiet water and reflected volcanic cycles, not glaciation. Rankin (1967Rankin ( , 1969 suggested a glacial origin for the laminated pebbly mudstones and associated muddy-matrix conglomerates (diamictites), a conclusion supported by Blondeau and Lowe (1972), Schwab (1976), and Miller (1986, 1989a.…”
Section: Previous Workmentioning
confidence: 92%
“…Schwab (1976) reported very rare striated clasts in the diamictite; I observed none. Both Rankin (1969) and Schwab (1976) noted the absence of a striated pavement, but pointed out that the diamictite everywhere rests on coeval subaqueous sediments (also implied in the lodgment till interpretation).…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the Crossnore Granite itself. Odom and Fullagar found that zircon U/Pb analyses reported earlier (Rankin et al, 1969) gave older ages (820 Ma) because of contamination from old Grenville gneisses that they assimilated.…”
Section: Rift Facies and The Cambrian Rift-to-drift Transition Transmentioning
confidence: 95%
“…Ultramafic rocks are confined to the sequence below the Catoctin, and a set of hornblende gabbros may also be confined to the preCatoctin sequence. Most of these rocks were originally included in the Crossnore plutonicvolcanic suite of Rankin and considered to be ~820 Ma (Rankin et al, 1969(Rankin et al, , 1973. Since then, additional isotopic dating indicates that the felsic peralkaline plutonic and volcanic rocks of the Crossnore type are older than -650 Ma and unconformably underlie the Lynchburg/Ashe formations (see section on Crossnore plutonic-volcanic suite).…”
Section: Rift Facies and The Cambrian Rift-to-drift Transition Transmentioning
confidence: 99%